Future studies of the Crisis Increases surface Temperature and Reduces the Climatic Comfort of Citizens in Tehran Metropolis - Hamideh Afsharmanesh; zahra hejazizadeh; Bohloul Alijani (تحقیقات کاربردی علوم جغرافیایی)
Climate predictions have been made in global, regional and local simulation, and climatic parameters have changed in terms of trends and models in climatology, futures studies are less visible in literature and climatology literature therefore environmental planning and futures analysis are an attempt to look at the long-term future in the field of climatology. Today, one of the most important challenges of the present and future is the increase in temperature and   is the lack of climatic comfort. The growth of Tehran's metropolitan area, improving living standards, expanding urbanization and industry, climate change, and the energy shortage crisis are important. The survey forms were prepared by the climatologists and managers of Tehran and data analysis, futuristic techniques such as scenario for data analysis tool in this study was MICMAC software. have been used. In the research process, the most important key factors and drivers in relation to futures studies were identified in relation to the increase of temperature in the city of Tehran. Mini scenarios and a comprehensive scenario were defined in three cases: